The Glass Is Half Full: The Need to Promote Positive Mental Health in Black College Students. Issue 3 (3rd July 2021) - Mushonga, Dawnsha R.
ABSTRACT: This article provides an overview of Black college students and the need to focus on promoting positive mental health (PMH). Traditionally, research examining Black student's mental health has occurred from a deficits-based perspective while failing to acknowledge their fortitude in persevering despite enduring adverse circumstances (i.e. racism and discrimination). PMH is comprised of social, emotional, and psychological well-being. More importantly, it buffers against mental illness which is important given the low help-seeking rates among Black students. To date, no studies have examined PMH exclusively in Black students; therefore, our understanding of their ability to flourish in the college setting remains limited. Focusing on PMH provides a holistic picture of Black student's mental health and aids in reducing the educational and health disparities that currently exist between Black and White students.